Persepsi Pranata Laboratorium pendidikan (PLP) terhadap Peranannya dalam Mendukung Kegiatan Praktikum di Fakultas Teknik Universitas Lampung - Kadek Adi Mahendra; Rino Erviana; Ni Wayan Puspa Apriana Susanti; Mutiara Ulul Azmi (CV. SINAR HOWUHOWU, 2026)
The success of practical courses at the Faculty of Engineering, University of Lampung, is determined not only by facilities and infrastructure but also by the role of laboratory education personnel (PLP) as learning facilitators. A gap exists regarding PLPs’ perceptions of their contribution to the smooth implementation of practical activities and the limitations of an integrated laboratory management system. This study aims to explore PLPs’ perceptions of their roles, identify challenges, and formulate recommendations to improve laboratory quality. The research employed a mixed-method approach with a descriptive design. The population consisted of all laboratory PLPs at the Faculty of Engineering, University of Lampung (sample of 7 participants). Data were collected using Likert-scale questionnaires and semi-structured interviews, then analyzed through descriptive quantitative and thematic approaches. The results indicate that PLPs are actively involved in preparing laboratory tools and materials, guiding student assistants, and understanding their strategic role in supporting the quality of learning. Challenges identified include limited PLP personnel, uneven workload distribution, and the lack of an integrated documentation system. The study recommends enhancing PLP training and competency development, establishing clear laboratory SOPs, implementing digital documentation systems, and balancing workload distribution to improve practical course quality and create a professional and sustainable laboratory environment.